Variation in energy metabolism arising from the effect of the tumor microenvironment on cell biological behaviors of bladder cancer cells and endothelial cells. (3rd October 2019) - Li, Dan; Jiao, Wei; Liang, Zhijuan; Wang, Liping; Chen, Yuanbin; Wang, Yonghua; Liang, Ye; Niu, Haitao
Abstract: Tumor energy metabolism and angiogenesis play significant roles in tumor genesis and development, while the effect of the tumor microenvironment (TME), which tumors rely on, is always ignored. In this research, we cocultured bladder cancer (BC) T24 cells with tumor‐associated human umbilical vein endothelial cells (HUVECs) under normoxic and hypoxic conditions and detected proliferation, migration, oxidative phosphorylation (OXPHOS) and glycolysis to reveal the energy metabolism characteristics and their effect on cell biological behaviors (CBBs) in the TME. Compared with single‐cultured cells, both cocultured T24 cells and HUVECs showed poor proliferation and migration in hypoxic environment, and OXPHOS was activated in cocultured T24 cells but weakened in cocultured HUVECs. However, in normoxic environment, cocultured T24 cells grew much faster while cocultured HUVECs grew slower compared with single‐cultured cells. Additionally, glycolysis played a crucial role in energy metabolism and was inhibited in cocultured T24 cells but activated in cocultured HUVECs. In normoxic TME, OXPHOS take main responsibility of energy metabolism. T24 cells exhibited increased proliferation and migration with HUVECs support. In hypoxic TME, glycolysis may be the primary energy supply pathway. T24 cells then exhibit suppressed proliferation and migration, while HUVECs tend to promote angiogenesis to adapt to the harsh TME.